2000
DOI: 10.1159/000028975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Events Implicated in Brain Tumor Angiogenesis and Invasion

Abstract: We have conducted studies designed to help elucidate the molecular mechanisms involved in brain tumor invasion and angiogenesis, which are critical in the growth of malignant tumors of the central nervous system. A variety of molecular factors have been implicated in these processes. Here we focus on three that are of particular importance in the progression of brain tumors. Angiopoietins are involved in the regulation of vascular development. Hypoxia inducible factor-1 is a transcription factor that up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 19 publications
2
62
0
1
Order By: Relevance
“…Human glioblastoma is a richly vascularised tumour (Zagzag et al, 2000) that expresses and actively releases in the vicine tissues substantial amounts of factors promoting new vessel growth (Guerin and Laterra, 1997). As a counterproof of such biological attitude of glioblastoma, we also found that VEGF is actively released by A172, U87MG and U373MG glioblastoma cells in the tissue culture media.…”
Section: Discussionmentioning
confidence: 58%
“…Human glioblastoma is a richly vascularised tumour (Zagzag et al, 2000) that expresses and actively releases in the vicine tissues substantial amounts of factors promoting new vessel growth (Guerin and Laterra, 1997). As a counterproof of such biological attitude of glioblastoma, we also found that VEGF is actively released by A172, U87MG and U373MG glioblastoma cells in the tissue culture media.…”
Section: Discussionmentioning
confidence: 58%
“…We and others have reported previously that FAK protein and activity (based on phosphorylation of Tyr 397 ) are elevated in grades III and IV malignant astrocytoma tumors (anaplastic astrocytoma and glioblastoma, respectively), compared with the normal brain (7,13). We have also shown that the overexpression of wild-type FAK promotes soft agar growth of glioblastoma cells (14), the expression of the mutant FAK397F inhibits soft agar growth of these cells (15), and that FAK is sufficient to promote Ras activity in glioblastoma cells propagated in aggregate suspension or as a monolayer (15).…”
Section: Fakmentioning
confidence: 90%
“…FIG. 13. Elevated expression of the transcription factor KLF8 with expression of wild-type FAK in glioblastoma cells propagated in vitro and in vivo.…”
Section: Ubiquitin-dependent Degradation Of P27mentioning
confidence: 99%
“…Recruitment or cooption of preexisting blood vessels by tumors, as previously described by Holash and colleagues, may represent one such mechanism (5)(6)(7). Early in tumor development, preexisting vasculature is engaged by growing tumor cells.…”
mentioning
confidence: 92%